Charpy impact property related to 100 cleavage fracture in 15CrODS steel. (November 2014) - Ukai, S.; Izawa, W.; Oono, N.; Hayashi, S.; Kohno, Y.; Ohtsuka, S.; Kaito, T.
<x content-type="archive" xml:space="preserve">Abstract</x> Based on the former results that delamination along 100 cleavage fracture leads to the improved absorbed energy, 100 cleavage plane was formed in parallel to the rolled plate by recrystallisation and cold roll processing in 15CrODS steel plate. Charpy impact properties were investigated in terms of notch direction against 100 cleavage plane. Notch with normal direction against 100 cleavage plane induced delamination fracture, but provided similar absorbed energy to that of conventional extruded bar. The transverse notch direction against 100 cleavage plane served higher absorbed energy at low temperature. Higher upper shelf energy and lower DBTT were attained in conventional hot extruded bar, which contains any crystallographic planes rotated around <110> axis at the transverse direction. The delamination fracture leading to high absorbed energy is significantly affected by a crystallographic morphology of the 100 cleavage plane perpendicular to transverse plane.